Synthesis, characterization and ESR spectroscopy of novel s-triazine bearing three oxygen-linked lutetium bisphthalocyanine sandwich complexes - (:unkn) unknown (WORLD SCI PUBL CO INC, 2005)
The conversion of compound 1 [2,4,6-tris(2-oxaphthalonitrile)-s-triazine] into its isoindoline derivative of 2,4,6-tris[2-oxa(1,3-hexaimino isoindoline)]-s-triazine 2 was accomplished by bubbling ammonia gas through a solution in methanol in the presence of sodium methoxide. The cyclization of two different isoindoline derivatives namely, compound 2 and 4,5-bis(hexylthio)-1,2-diimino-isoindoline 3 with lutetium(III) acetate, [Lu(OAc)(3)] in refluxed DMF by the method of statistically mixed condensation gave trimeric trilutetium phthalocyanine [(LuOAc)(3)(Pc)(3)] 4. [Lu-3(Pc)(6)] 5 has been synthesized in situ by the reaction of phthalocyanine 4 and three equivalents of dilithium octakis-hexylsulfanyl phthalocyanine in amyl alcohol. Copyright (C) 2005 Society of Porphyrins & Phthalocyanines.
Keywords: phthalocyanine; sandwich; lutetium; electron spin resonance; PHTHALOCYANINE COMPLEXES; CHIRAL 1,2-NAPHTHALOCYANINES; ELECTROCHEMICAL PROPERTIES; COBALT PHTHALOCYANINE; ELECTRICAL-PROPERTIES; ABSORPTION-SPECTRA; CRYSTAL-STRUCTURE; REDOX PROPERTIES; DIPHTHALOCYANINES; MACROCYCLES